Effectiveness of Virtual Reality dan Digital Simulation in Medical Education: A Scoping Review Clinical Competency Development - Ellyzar, Fildzah Ayudya; Septiaci, Rindaris; Himawan , Wildan; Muhajir , Keiza Aryanti; Putri, Haura Febriyanti (Cirebon Annual Multidiciplinary International Conference (CAMIC), 2026)
The digital transformation in medical education is driving the use of technologies such as Virtual Reality (VR) and digital simulations as tools for learning clinical skills. These technologies help students learn in a safe environment. In addition to clinical skills learning, technology is also being used in other competency learning, such as cognitive and affective aspects. However, a comprehensive evaluation of the effectiveness, barriers to implementation, and long-term impacts of these technologies is needed. This study aims to examine the scientific evidence regarding the influence of VR and digital simulations on medical students' mastery of competencies such as clinical skills, cognitive aspects, and affective aspects. This study used a scoping review approach by searching for articles from several databases such as PubMed, SpringerLink, and Google Scholar. Article selection was based on predetermined inclusion and exclusion criteria, with study quality assessed using the JBI and MERSQI instruments. Seven articles were eligible for review. Results showed that using VR increased the chance of passing exams by up to 85% compared to conventional learning methods. VR is used in various fields such as anatomy learning, Problem-Based Learning (PBL), clinical skills training, and OSCEs. Furthermore, VR contributes to the development of student empathy through immersive simulations. Conclusion: Virtual Reality technology and digital simulation have a positive impact on medical students' achievement. Despite its many benefits, the implementation of this technology still requires careful planning and further research on its cost-effectiveness and long-term impact.